SISTEM USAHA PERIKANAN TANGKAP DI KABUPATEN KULON PROGO, DAERAH ISTIMEWA YOGYAKARTA - Yunistia Renofati; Tri Wiji Nurani; John Haluan (Institut Pertanian Bogor, 2009)
Kulon Progo's Regency constitutes one of region at Yogyakarta’s Province who have potency of fishery resources that needs to be developed. Fishery effort at Kulon Progo's Regency starts amends on year 2000 by wreaked its fishermen from outside regions, one of it comes from Cilacap. This effort can pull local society for tries at the fishery area, although with medium and infrastructure that still circumscribed. System approximate methods is utilized to analize fishery catches effort’s system at Kulon Progo's Regency. Effort’s analyze include type establishment fishes out superior, effort productivity, technical aspect, social aspect, and financial aspect. SWOT’s analyze is utilized to determine strategy alternative and fishery effort catches development at Kulon Progo's Regency. Result of the researches pointed that type fishes out superior at Kulon Progo’s Regency is tigawaja fishes (Johnius dussumieri), white pomfret (Pampus argentus), and lobster (Panulirus sp.). Averagely haul productivity have gyration among 19,96 until with 32,22 kg per trip per year. Tool catches in point be utilized is sirang's net or bottom gillnet. Kulon Progo's Regency society works as farmer. Profession as fisherman constitutes to main part time work of large part society at kulon Progo. Acquired effort of bottom gillnet as big as Rp 132.812.500 per year, Ratio per Cost as big as 1,68 per year, and Payback Period as big as 0,24 year. Strategy alternative which one that as priority in develop fishery catches effort in Kulon Progo, which is increasing medium and infrastructure of production, increasing arrest fleet, increasing human resources quality of fishery, and accelerate landing base fishes development.Key words: fisheries catch effort, Kulon Progo, system approaching